2016
DOI: 10.1097/mpg.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Cyproheptadine Use in Children With Functional Gastrointestinal Disorders

Abstract: Cyproheptadine effectively improves symptoms of Rome III-defined FGIDs and has a good safety profile when used for these indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 27 publications
0
37
0
3
Order By: Relevance
“…Worawattanakul et al 12 studied the role of cyproheptadine in abdominal migraine prophylaxis in 12 patients, and 10 of these patients had fair to excellent response. Madani et al 10 demonstrated complete resolution of symptoms in 13 of 18 patients with AM treated with cyproheptadine (72% response rate). Lewis 55 noted that cyproheptadine is a simple, effective, and safe treatment option for AM in children younger than age 10 years who are not overweight.…”
Section: Abdominal Migrainementioning
confidence: 98%
See 4 more Smart Citations
“…Worawattanakul et al 12 studied the role of cyproheptadine in abdominal migraine prophylaxis in 12 patients, and 10 of these patients had fair to excellent response. Madani et al 10 demonstrated complete resolution of symptoms in 13 of 18 patients with AM treated with cyproheptadine (72% response rate). Lewis 55 noted that cyproheptadine is a simple, effective, and safe treatment option for AM in children younger than age 10 years who are not overweight.…”
Section: Abdominal Migrainementioning
confidence: 98%
“…47 Cyproheptadine, a nonselective antagonist of 5-HT2A and 5-HT2B, has not been formally studied in FD in humans. 18 To date, there are only two published retrospective studies (Madani et al 10 and Rodriguez et al 11 ) that showed efficacy of cyproheptadine in a majority of children diagnosed with Rome IIIdefined FD (77% and 55% resolution of symptoms, respectively).…”
Section: Functional Dyspepsiamentioning
confidence: 99%
See 3 more Smart Citations